Highly substituted 2,3,7,8,12,13,17,18-octaethylporphyrins with meso aryl residues - SENGE, MATHIAS (My University, 2010)
Highly substituted porphyrin-bearing meso aryl groups are useful compounds for optical applications and for studies on the interrelationship between the substituent pattern, macrocycle conformation and physical properties. They serve as biomimetic models for the function of tetrapyrroles in nature and help to elucidate modulation of cofactor properties through conformational effects. Using a sequence of lithium organic substitution reactions the synthesis of novel free base 5,10-A2- and 5,10-AB-2,3,7,8,12,13,17,18-octaethylporphyrins bearing donating groups such as ?OMe and ?NMe2 on the aryl-substituent was achieved. Larger aromatic residues (1-naphthyl, 9-anthracenyl and 9-phenanthrenyl) could be introduced into the macrocycle system as well, and these systems were used for the preparation of highly substituted porphyrins with a mixed substituent pattern. Using phenanthrenyl derivatives, the complete series of meso phenanthrenyl substituted octaethylporphyrins was successfully synthesized and the palladium complexes were prepared for photophysical investigations. Structural studies clearly showed the influence of individual substituents on the conformation of the tetrapyrrole macrocycle and conformational analyses revealed the variation of the underlying distortion modes depending on the type and arrangement of the meso substituents.
PUBLISHED
Keywords: Chemistry